2021
DOI: 10.1002/lt.26335
|View full text |Cite
|
Sign up to set email alerts
|

Use of Livers With Fibrosis Based on Donor Hospital Biopsy: Missed Opportunities?

Abstract: Despite increases in the number of deceased donors in the United States, the donor supply fails to meet the ever-increasing demand. Centers have had to increase use of "marginal" liver grafts to increase the number of deceased donor liver transplantations (DDLTs). The term marginal has been used to describe donors with significant macrosteatosis, advanced age, donations after circulatory death, and split livers, for which a lot of data exist in the field of liver transplantation. (1) However, there are little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…20 Furthermore, in a more contemporary national retrospective study of the OPTN/UNOS database, Narasimman et al also demonstrated no significant association between Ishak level of fibrosis and 3, 6, 12, 24, or 36 month graft survival. 12 High degrees of fatty infiltration, as indicated by ≥ 30% macrovesicular steatosis, however, have demonstrated varying results in portending worse recipient outcomes. This discrepancy is well known and has been discussed previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, in a more contemporary national retrospective study of the OPTN/UNOS database, Narasimman et al also demonstrated no significant association between Ishak level of fibrosis and 3, 6, 12, 24, or 36 month graft survival. 12 High degrees of fatty infiltration, as indicated by ≥ 30% macrovesicular steatosis, however, have demonstrated varying results in portending worse recipient outcomes. This discrepancy is well known and has been discussed previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, consensus has not been uniformly achieved. Specifically, previous studies have not uniformly agreed upon an association with the poorer 1‐year graft survival and high degrees (≥30%) of macrovesicular steatosis, 7,9,11 while relationships with fibrosis 12–14 and inflammation 15,16 identified on donor liver biopsy similarly remain unclear. Indeed, no systematic standard exists delineating which donors should receive biopsy, and the impact of biopsy findings remains provider dependent 17 …”
Section: Introductionmentioning
confidence: 99%
“…11 Liver fibrosis on donor liver biopsy was assessed according to the Ishak score, which ranges from 0 to 6. 13,15 Significant liver fibrosis was defined as those with an Ishak score ≥3. 11 Macrosteatosis on donor liver biopsy was categorized as no (<5%), mild (5%–29%), moderate (30%–60%), and severe (≥60%).…”
Section: Methodsmentioning
confidence: 99%
“…12 Because biopsies are usually not performed until cross-clamp is achieved in DCD LT, the time allotted for obtaining a biopsy and awaiting its results prolongs cold ischemia time (CIT). Recently, Narasimman et al 13 reported that, although liver fibrosis on donor biopsy increased the rate of graft discard, it did not compromise transplant outcomes. Because of time constraints in DCD LT and the limited impact on transplant outcomes, the utility of biopsy on DCD LT warrants evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In this most recent issue of Liver Transplantation , Narasimman et al examined liver biopsy data from the time of procurement in the United Network for Organ Sharing (UNOS) Standard Transplant Analysis and Research (STAR) file from December 24, 2014, to June 11, 2020, a period when roughly 45,000 liver transplantations were performed in the United States. ( 2 ) Biopsies were performed in 19,947 donors, and 15,130 of these livers (roughly one‐third of all liver transplantations performed) were transplanted. The remaining 4817 (24.1%) were discarded.…”
mentioning
confidence: 99%